Pollen morphology of the genus Pyrus (Rosaceae) in Iran - Zamani, Asghar; Attar, Farideh; Maroofi, Hossein (Acta Biologica Szegediensis, 2010)
In this study, pollen morphological characters of nine species of the genus Pyrus L. belonging to four sections, Argyromalon, Pashia, Pyrus and Xeropyrenia were examined by light (LM) and scanning electron (SEM) microscope. Regarding pollen shape, two forms can be recognized in the same specimen: the first form ranges from prolate- spheroidal, subprolate to prolate, while the second form includes triangular, trilobate and circular shapes, the apertures structure usually consists of three ectocolpi and three endopores. colpi occupy 85- 91% of length of pollen, often arranged meridionally but also parallel pattern can be recognized, endopore is located in the middle of colpi. Regarding sculpturing of the exine in proximal face, striate sculpturing is observed that according to some characters such as degree of slope of ridges, percentage of ridges and perforations, diameter of perforations is subdivided to four main types. Results of pollen grain fertility studies in the genus showed high percentage of fertility among studied species except in one species.